Bone-seeking nanoplatform co-delivering cisplatin and zoledronate for synergistic therapy of breast cancer bone metastasis and bone resorption - Yanjuan Huang; Zhanghong Xiao; Zilin Guan; Zishan Zeng; Yifeng Shen; Xiaoyu Xu; Chunshun Zhao (Elsevier, 2020)
The "vicious cycle" established between tumor growth and osteolysis aggravates the process of breast cancer bone metastasis, leading to life-threatening skeletal-related events that severely reduce survival and quality of life. To effectively interrupt the "vicious cycle", innovative therapeutic strategies that not only reduce osteolysis but also relieve tumor burden are urgently needed. Herein, a bone-seeking moiety, alendronate (ALN), functionalized coordination polymer nanoparticles (DZ@ALN) co-delivering cisplatin prodrug (DSP) and antiresorptive agent zoledronate (ZOL) via Zn2+ crosslinking for combination therapy was reported. The versatile DZ@ALN with a diameter of about 40 nm can cross the fissure in the bone marrow sinus capillaries, and possesses an excellent bone-seeking ability both in vitro and in vivo. Additionally, DZ@ALN could synergistically inhibit the proliferation of cancer cells, suppress the formation of osteoclast-like cells and induce the apoptosis of osteoclasts in vitro. Importantly, it could preferentially accumulate in bone affected site, remarkably inhibit the proliferation of tumor cells, relieving bone pain, and significantly inhibit the activation of osteoclasts, protecting the bone from destruction in vivo, eventually leading to the breakdown of "vicious cycle" without inducing obvious systemic toxicity. This innovative nanoagent combines chemotherapy and osteolysis inhibition, exhibiting an inspiring strategy for effective treatment of bone metastasis.